2011
DOI: 10.1088/0022-3727/44/15/155204
|View full text |Cite
|
Sign up to set email alerts
|

He plasma pretreatment effects on oxygen plasma-induced carbon loss and surface roughening in an ultralow-k organosilicate glass film

Abstract: Ex situ Fourier transform infrared spectroscopy (FTIR), x-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM) have been used to characterize the effects of He plasma pretreatment on O2 plasma-induced modification of the surface composition and structure of nanoporous ultralow dielectric constant (k) organosilicate glass (OSG) films. Oxygen plasma induces Si–C bond scission and carbon abstraction, and increased k values. Carbon abstraction exhibits diffusion-dominated kinetics. FTIR data, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…2(a), bottom trace] can be decomposed into two spectral components with binding energies of $284 eV and 285 eV, corresponding to Si-C and C-C bonding environments, respectively. 2,19 Similarly, N(1s) spectra Fig. 2 6,20 therefore, it is difficult to resolve both features in the same spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…2(a), bottom trace] can be decomposed into two spectral components with binding energies of $284 eV and 285 eV, corresponding to Si-C and C-C bonding environments, respectively. 2,19 Similarly, N(1s) spectra Fig. 2 6,20 therefore, it is difficult to resolve both features in the same spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Ion bombardment enhances the formation of a SiO 2 -like layer in O 2 plasma. [106,107] Using the Vienna Ab initio Simulation Package, Chaudhari et al [108][109][110] found that the lowest activation energy of Si-CH 3 bond scission and Si-O formation is 0.1 eV, resulting in the formation of H 2 O and Si-OH. Recently, Rimsza et al [111] performed a molecular dynamics simulation using reactive force field and LAMMPS package and showed that Si-O-Si linkages correlate with increasing Si-OH fraction and decreasing Q 4 that porosity includes T 3 and D 2 units.…”
Section: Plasma-induced Damagementioning
confidence: 99%
“…The fundamental mechanism of the plasma‐induced damage of SiOC films in oxygen plasma was studied by Goldman et al Oxygen atoms penetrate and diffuse into SiOC films, damaging SiOC via Si‐OH formation. Ion bombardment enhances the formation of a SiO 2 ‐like layer in O 2 plasma . Using the Vienna Ab initio Simulation Package, Chaudhari et al found that the lowest activation energy of Si‐CH 3 bond scission and Si‐O formation is 0.1 eV, resulting in the formation of H 2 O and Si‐OH.…”
Section: Process Optimizations and Improvementsmentioning
confidence: 99%